¿Era tan pre-crítico el Kant precrítico? Posiciones no dogmáticas en la reflexión sobre el conocimiento - POSADA KUBISA, María Luisa (Revista de Filosofía, 2011)
This article rereads some of Kant’s writings considered as pre-critical. It tries to investigate how in them the reflection about knowledge progressively takes a new direction against dogmatic positions. In order to do this, this article focuses on some of its specific aspects. We cannot assimilate these works to the revolution that the KrV will signify but we can read them as a preparation for that critical field. We share those interpretations which think that there is more continuity than breaking off between the Kant considered pre-critical and his deployment clearly critical.
Keywords: Dogmatism; Empiricism; Pre-critical Kant; KrV; Sensitive-intelligible